2020
DOI: 10.3390/ijerph17113987
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Patients with Non-Communicable Diseases for Primary Healthcare Facilities: A Discrete Choice Experiment in Wuhan, China

Abstract: Objectives: To elicit stated preferences of patients with non-communicable diseases (NCDs) for primary healthcare (PHC) facilities and to explore the willingness-to-pay (WTP) for facility attributes. Methods: A discrete choice experiment (DCE) was conducted through face to face interviews. The DCE survey was constructed by five attributes: type of service, treatment measures, cost, travel time, and care provider. Patients’ preferences and willingness to pay for facility attributes were analyzed using a mixed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 45 publications
4
25
1
Order By: Relevance
“…15 These factors were also found in studies that reviewed the access, availability, and affordability of healthcare in South Africa [15][16][17][18][19] and in other countries including Albania, China, Iran, Jordan, Nigeria, Pakistan, Spain, Tanzania, and Uganda. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] A list of possible attributes to be presented to the participants was compiled, with the concurrence of the Northern Tygerberg substructure team, resulting in the finalization of the pregroup discussion list. Table 1 summarizes articles from which the attributes were retrieved, mainly from South African-related articles, thus providing a glimpse into patient preferences in the country of study.…”
Section: Selection Of Attributes List For Group Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These factors were also found in studies that reviewed the access, availability, and affordability of healthcare in South Africa [15][16][17][18][19] and in other countries including Albania, China, Iran, Jordan, Nigeria, Pakistan, Spain, Tanzania, and Uganda. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] A list of possible attributes to be presented to the participants was compiled, with the concurrence of the Northern Tygerberg substructure team, resulting in the finalization of the pregroup discussion list. Table 1 summarizes articles from which the attributes were retrieved, mainly from South African-related articles, thus providing a glimpse into patient preferences in the country of study.…”
Section: Selection Of Attributes List For Group Discussionmentioning
confidence: 99%
“…Some studies did not quite mirror the attributes extracted from our group discussions, possibly caused by different objectives and study methodologies. Studies in South Africa, 9 China, 21,25,26,29,30 India, 20 Iran, 27 Jordan, 33 Spain, 28 and Albania 44 included age, education, employment, travel time, transport costs, chronic illness, medication availability, illness gravity, accessibility, type of service provided, previous experience, care providers, and facilities infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were consistent with Honda et al [ 5 ], of which drug availability was identified as the most important issue. The literature demonstrates treatment measures to be the most important factors that affect healthcare seeking [ 28 ]. This study reveals that patients have preferences for certain characteristics of health facilities: near (short distances to health facility), with absolute confidentiality during visits, with short first visit waiting and appointment waiting time, where treatment is offered by doctors, and where all required medication is available.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is a large body of work on stated preferences, only a few studies have been conducted regarding patients’ choice of facility, specifically within public health care. A systematic review of DCEs used to elicit patient preferences for primary healthcare showed that most studies were American or European, and focused on general practitioner (GP) consultations, [ 26 ] while Chinese studies appeared to focus primarily on the public health preferences of rural populations [ 27 , 28 , 29 , 30 ]. Only one South African DCE of public health facility preferences was identified [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are ultimately intended to extrapolate respondents’ preferences starting from their stated preferences in hypothetical scenarios [ 89 ]. The authors selected such a kind of experiment with the aim to identify adolescents’ preferences for PA so as to allow the design of effectively tailored health promotion policies, because discrete choice models are considered as one of the most adequate techniques for preferences elicitation [ 90 , 91 ].…”
Section: Methodsmentioning
confidence: 99%